2020
DOI: 10.1016/j.ejpoleco.2020.101925
|View full text |Cite
|
Sign up to set email alerts
|

Perception vs. experience: Explaining differences in corruption measures using microdata

Abstract: Understanding corruption is at the heart of treating the dysfunctionality of many countries' public sectors. Yet, most corruption research suffers from one common problem: There is no "objective" measure of public-sector corruption for a cross-section of countries. Most studies on the determinants or the effects of corruption rely on indicators of corruption perception. In recent years, a second type of indicator reflecting stated experiences with bribery has become available. If corruption perception is prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 66 publications
(55 reference statements)
1
28
0
Order By: Relevance
“…As a result, many Indonesians feel disappointed with this regulation, which results in the KPK feeling that it no longer has independence in guarding corruption crimes. This is in accordance with the opinion of experts who reveal that the role of law in dealing with corruption greatly determines transparency in a government [21,22]. In addition, the role of the president is very helpful in the successful handling of corruption risks.…”
Section: Resultssupporting
confidence: 85%
“…As a result, many Indonesians feel disappointed with this regulation, which results in the KPK feeling that it no longer has independence in guarding corruption crimes. This is in accordance with the opinion of experts who reveal that the role of law in dealing with corruption greatly determines transparency in a government [21,22]. In addition, the role of the president is very helpful in the successful handling of corruption risks.…”
Section: Resultssupporting
confidence: 85%
“…Relatively speaking, however, obtaining insights into corruption experience or corruption incidence is more challenging than gathering information into corruption perceptions. This distinction can prove crucial in some cases (Belousova et al 2016;Gillanders and Parviainen 2018;Gutmann et al 2020;Olken 2009), and the present research adds some new insights in this regard.…”
Section: Introductionmentioning
confidence: 57%
“…Related measurement issues have been noted in numerous studies (Donchev and Ujhelyi 2014;Goel and Nelson 2011). It had also been observed that there might be a difference between corruption perceptions and actual corruption (Belousova et al 2016;Donchev and Ujhelyi 2014;Gillanders and Parviainen 2018;Gutmann et al 2020;Olken 2009). The present research can be seen as somewhat straddling both perceptions and actual corruption-the respondents to the survey that forms the basis of our dataset were managers/owners of firms who were asked questions about both their experiences with bribery/ corruption and the assessment regarding the degree to which such activity hinders their business operations.…”
Section: Theoretical Backgroundmentioning
confidence: 89%
See 1 more Smart Citation
“…In quantitative terms, corruption studies are scarce, because there are no unique measures of corruption, and they are usually based on perception surveys. However, the correlation between different corruption indices is high, so there is a consensus in terms of the definition of corruption, Mauro (1995), Gutmann et al (2020) and Ojeka et al (2019). The aggregate effect of corruption on economic growth has been studied in the literature.…”
Section: Introductionmentioning
confidence: 99%